Gestational Outcomes of Pregnant Women Who Have Had Invasive Prenatal Testing for the Prenatal Diagnosis of Duchenne Muscular Dystrophy. (30th July 2018) - Beksac, Mehmet Sinan; Tanacan, Atakan; Aydin Hakli, Duygu; Orgul, Gokcen; Soyak, Burcu; Balci Hayta, Burcu; Dincer, Pervin; Topaloğlu, Haluk
Abstract : Aim . To show the importance of prenatal diagnosis of Duchenne Muscular Dystrophy (DMD) and to demonstrate the effect of DMD gene mutations on gestational outcomes. Materials and Methods . We retrospectively evaluated 89 pregnancies in 81 individuals who were referred to Hacettepe University for prenatal diagnosis of DMD between January 2000 and December 2015. Prenatal diagnostic methods (chorionic villus sampling (CVS): 66, amniocentesis (AC): 23) were compared for test results, demographic features, and obstetric outcomes of pregnancies. The female fetuses were divided into two groups according to the DMD status (healthy or carrier) to understand the effect of DMD gene mutations on obstetric outcomes. Results . Eight prenatally diagnosed disease-positive fetuses were terminated. There was no statistically significant difference between the CVS and AC groups in terms of study variables. There were 46 male fetuses (51.6%) and 43 female fetuses (48.4%). Fifteen of the female fetuses were carriers (34.8%). Median birthweight values were statistically insignificantly lower in the carrier group. Conclusion . Pregnancies at risk for DMD should be prenatally tested to prevent the effect of disease on families and DMD carrier fetuses had obstetric outcomes similar to DMD negative female fetuses.